(untitled) (Szociológiai Szemle, 2023)
The paper focuses on inter-organisational networking in a cross-border cooperation (CBC) setting. A tri-border region at an EU periphery is examined in the inquiry related to the drivers of cross-border network formation. The question is addressed why linkages between certain organisations materialise and what their motivational and enabling context is. Generic network theory serves only as a starting point: the contextual embeddedness of network-actors and the intriguing combinations of their various types and motivations persuaded the authors to adjust and combine existing conceptualisations. Explanations for inter-organisational linkages are put forward as theoretical assertions potentially rooted in social-economic peculiarities of the diverse geographical and cultural settings where CBC networks emerge. The authors wish to provoke further thinking by introducing a new perspective in both border studies and inter-organisational network analysis which could assist with understanding what lies behind existing structures.